Network connectivity based power-aware routing algorithm for Mobile Ad Hoc Networks. (14th March 2011) - Varaprasad, G.
Mobile Ad Hoc Network (MANET) is a decentralised network, which consists of mobile nodes. In this paper, we propose an efficient routing algorithm for the MANETs. Here, we use two metrics namely minimum total transmission power and network connectivity over the network. The proposed work has been simulated using .Net and has compared with the existing algorithms such as DSR, Minimum Total Transmission Power Routing (MTPR) and Min-Max Battery Cost Routing (MMBCR). The simulation results have proved that the proposed model has reached at top position in terms of the number of nodes with zero-remaining energy and throughput. If the mobility of the node is 25 m/s, then the proposed model, MTPR model, MMBCR model and AODV model have transmitted 68%, 50%, 59% and 62% of the data packets, respectively. At 700 s, the number of nodes with zero-remaining energy in the proposed model is 5, whereas in the AODV model, MTPR model and MMBCR model the number of nodes with zero-remaining energy was 39, 22 and 7, respectively.